Food hygiene and food safety practices of households in a township north of Tshwane, Gauteng - Mashudu Manafe; Reno E. Gordon; Lindiwe J. Ncube (AOSIS, 2023)
Background: Foodborne illness is still a major public health concern worldwide. Most cases of foodborne illness can be traced to the home. The food safety practices of food handlers in the household are an important determining factor in food safety at the household level. Aim: To assess the food safety practices of food handlers in households in Ga-Rankuwa, Tshwane. Setting: The study was conducted in zones 1-9 and zone 16, as well as extension 25 of Ga-Rankuwa, Tshwane. Methods: A quantitative descriptive study design was used for which a structured questionnaire was administered among 339 food handlers. Descriptive and inferential statistical analysis was performed in STATA 13.1. Results: The majority of food handlers reported always washing their hands before (81%) and after handling raw meat, chicken or fish; the majority of food handlers (69%) reported always washing preparation surfaces and utensils with clean, soapy water after handling raw meat, chicken or fish. Less than half (45%) of food handlers reported never thawing frozen meat, chicken or fish in a bowl of cold water. Conclusion: The food handlers reported appropriate food safety practices regarding hand washing and food preparation surfaces and utensils. However, their practices regarding the storage of meat, chicken and fish were inappropriate. Contribution: This study builds on the existing body of literature on the food safety practices of food handlers. Moreover, the study findings can serve as a basis for the development of interventions to ensure food safety at a household level.